Penerapan Otomatisasi Penerangan Jalan Umum Tenaga Surya (PJU-TS) Untuk Energi Berkelanjutan di Desa Sri Agung Lampung Tengah - Ubaidah; Ahmad Saudi Samosir; Sony Ferbangkara; Martinus; Al Fariziy, M. Naufal (Nemui Nyimah, 2025)
Desa Sri Agung, Kecamatan Padang Ratu, Kabupaten Lampung Tengah, faces issues with several road sections where the street lighting system is not functioning to enhance nighttime visibility. To address this problem, Solar-Powered Public Street Lighting (PJU-TS) was installed. This system utilizes a Light Dependent Resistor (LDR) to detect light intensity and employs an IC 7805 as a voltage regulator. The PJU-TS lights automatically turn on at night in dark environmental conditions and turn off during the day by utilizing solar energy as the primary power source, thereby reducing dependence on conventional electricity. This activity consists of several methodological steps, including field surveys, system design, installation, and performance evaluation of the PJU-TS. The installation was carried out in two strategic locations involving the local community at several points along the roads in Sri Agung Village.. The evaluation results indicate that the PJU-TS system functions optimally to improve road visibility. However, there are still issues with the energy storage battery capacity, which remains small and affects lighting duration. The implementation of public street lighting with Solar Technology (PJU TS) in Sri Agung Village has had a significant impact on improving accessibility, security, and energy efficiency. Additionally, it helps promote energy sustainability and raises public awareness of the use of environmentally friendly technology.